The Anti-Inflammatory Role of Omega-3 Polyunsaturated Fatty Acids Metabolites in Pre-Clinical Models of Psychiatric, Neurodegenerative, and Neurological Disorders - Giacobbe, Juliette; Benoiton, Bonnie; Zunszain, Patricia; Pariante, Carmine M.; Borsini, Alessandra (Frontiers in Psychiatry, 2020)
Inflammation has been identified as one of the main pathophysiological mechanisms underlying neuropsychiatric and neurodegenerative disorders. Despite the role of inflammation in those conditions, there is still a lack of effective anti-inflammatory therapeutic strategies. Omega-3 polyunsaturated fatty acids (n-3 PUFAs) can reduce depressive symptoms and exert anti-inflammatory action putatively by the production of distinct n-3 PUFA-derived metabolites, such as resolvins D (RvD) and E (RvE) series, maresins (MaR) and protectins (PD), which are collectively named specialised pro-resolving mediators (SPMs) and act as strong anti-inflammatory agents. In this review we summarise evidence showing the effects of treatment with those metabolites in pre-clinical models of psychiatric, neurodegenerative and neurological disorders. A total of 25 pre-clinical studies were identified using the PubMed database. Overall, RvD and RvE treatment improved depressive-like behaviours, whereas protectins and maresins ameliorated neurological function. On a cellular level, RvDs increased serotonin levels in a model of depression, and decreased gliosis in neurodegenerative disorders. Protectins prevented neurite and dendrite retraction and apoptosis in models of neurodegeneration, while maresins reduced cell death across all studies. In terms of mechanisms, all SPMs down-regulated pro-inflammatory cytokines. Resolvins activated mTOR and MAP/ERK signalling in models of depression, while resolvins and maresins activated the NF-κB pathway in models of neurodegeneration and neurological disorders. Our review indicates a potential promising approach for tailored therapy with n-3 PUFAs-derived metabolites in the treatment of psychiatric, neurodegenerative and neurological conditions.